Experimental characterisation of CCD cameras for HREM at 300 kV - Meyer, R; Kirkland, A; Dunin-Borkowski, R; Hutchison, J (2000)
The modulation transfer function, noise transfer function and detection quantum efficiency of both 1k2 and 2k2 cameras attached to the same 300 kV FEGTEM have been measured. The results show that both the MTF and the DQE of the 2k2 camera are lower than for the 1k2 camera at frequencies above a third of the Nyquist limit. This lower per-pixel performance of the 2k2 camera is primarily a result of the use of a thicker phosphor scintillator. However, MTF and DQE of the 2k2 camera operated as an effective 1k2 camera by using 2 x 2 pixel binning are superior to the 1k2 camera in the medium spatial frequency range. (C) 2000 Elsevier Science B.V.